DIKSI DALAM TEKS BERITA SISWA KELAS VIII SMP NEGERI 6 PARIAMAN - Pendary, Vonny Julia; Amir, Amril (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this study were. (1)to describe the accuracy of diction in the news text of class VIII students of  SMP Negeri 6 Pariaman. (2)to describe the precision of diction in the news text of class VIII students of  SMP Negeri 6 Pariaman. This type of research is qualitative research with descriptive methods. This research was conducted at Pariaman State Middle School 6. The data of this study are qualitative data in the form of news text diction. The source of this research data is text news writing for class VIII students of SMP Negeri 6 Pariaman. The instrument of this research is the researchers themselves. The technique of collecting data is through documentation studies. The technique of validating the data in this study is the cross-check technique. The data are analyzed by steps, namely (1) the researcher identifies the diction contained in the news text, (2) analyzes the text based on the aspects studied, (3) analyzes the data based on the exact and accurate inaccuracies, and (4) makes conclusion. Kata kunci: Diksi, Ketepatan, Kecermatan, Teks Berita